Edukasi Masyarakat terhadap Penyakit Diabetes Militus di Posyandu Lansia Kelurahan Margorejo, Kota Metro - Supardi; Ludiana; Inayati, Anik (Jurnal Pengabdian Dharma Wacana, 2025)
Diabetes mellitus is disease chronic requiring maintenance long medical, with method control level sugar blood for the occurrence complications of diabetes The 2014 Sample Registration Survey stated that diabetes is becoming murderer number three in Indonesia. Then, the prevalence of diabetes in Indonesia tends to increased, namely from 5.7 % in 2007 to 6.9 % in 2013. More astonishing again, like released Ministry Health (Ministry of Health), 2/3 of diabetics (term for sufferer diabetes) in Indonesia does not know himself have diabetes. Objective devotion public This For give knowledge to public for guard his health so that no caught DM disease, and if has hit How the solution care for sugar his blood in normal range so his life become more quality. Activity done during two One month in the village Margorejo South Metro District. Results​ activity obtained happen improvement knowledge DM disease pre-post education, where as many as 37 participants (82.2%) were knowledgeable good. education health capable increase knowledge DM disease about How method apply pattern life and pattern healthy eating. Education​ should done education health in a way sustainable for the sake of creation more optimal health.